Analisis Indeks Kepuasan Masyarakat Pada Mall Pelayanan Publik Kota Bekasi Tahun 2020 - Indah Wahyu Maesarini; Dodi Rahmat Setiawan; Diana Prihandini (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study wants to know and analyze the index of community satisfaction with public services at the Bekasi City Public Service Mall. In practice, the sources of information for this research are called informants who are interviewed as a data collection technique, they are figures who are considered capable of providing information related to the concepts being studied, other techniques used are observation and document review. Based on the discussion of the research results, it is concluded that the Bekasi City Public Service Mall in general has been running well according to the applicable rules and regulations, but not yet optimal, namely regarding the building infrastructure which is the place for the Bekasi City Service Mall which is not strategically located on the border of Bekasi City. not in a city that is the center of administrative and environmental activities for the residents of Bekasi City